JSA dan IBPRP Berdasarkan Permen PUPR No. 10 Tahun 2021 pada Proyek Jembatan Ruas–Mangun Jaya– Bts. Kab. Muba/Bts. Kab. Mura–Muara Beliti - Dony, Wari; Fadilla, Muhammad Akbar (Universitas Batanghari Jambi, 2025)
Workplace hazards can occur when the work environment causes injury, illness, or death. This danger can originate from many aspects including equipment, hazardous materials, processing processes, and work procedures. One of the risks of occupational hazards that occurs in a job is a work accident. The purpose of this research is to determine the identification of hazards and prevention carried out on the Section - Mangun Jaya - Bts Bridge Project. Muba District/Bts. District Mura – Muara Beliti and to analyze JSA and IBPRP based on PUPR Ministerial Decree No. 10 of 2021 on the Section – Mangun Jaya – Bts Bridge Project. Muba District/Bts. District Mura – Muara Beliti. The method used in this research is descriptive qualitative, namely trying to explain the condition of the subject and explain the real conditions that exist in the field. The data collection techniques used in this research are literature study, observation and interviews. Research steps carried out using the IBPRP method. The research results show that the results of risk analysis based on JSA show that there are 5 K3 policies that are declared very important and 4 K3 policies that are declared important. The highest score is for the statement